Harnessing Informal Communication: The Key to Building Trust and Agility in Remote Teams - Agus R, Abu Hasan; Nur Aini, Tsamar; Sholihah, Imroatus; Lisah, Nora; Mubarok, Shofil (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This research focuses on the role of informal communication in building team cohesion and trust in non-profit organizations. This research explores the mechanisms behind spontaneous and unstructured interactions that support decision-making, conflict resolution, and collective performance. This topic is relevant in the era of dynamic work, where the success of organizations increasingly depends on interpersonal relationships and cross-functional collaboration. This study uses a qualitative method with a case study approach involving in-depth interviews, direct observation, and internal document analysis. Data was collected from team members with diverse roles and experiences, including project managers, field coordinators, administrative staff, and senior volunteers. The analysis process includes data reduction, presentation of data in thematic matrices, and verification through source triangulation. This approach provides an in-depth understanding of the dynamics that affect team cohesion and collective trust. The results show that informal communication increases team trust and cohesion. Team members who frequently engage in spontaneous conversations show a better understanding of common goals, can better resolve conflicts, and show higher trust. Well-documented organizational documents also help reinforce successful work patterns, ensuring the continuity of best practices. The implications of this study include the importance of creating a work environment that encourages informal communication and makes strategic use of organizational documentation. The study provides relevant insights for developing collaboration strategies in the workplace and offers a foundation for further research on interpersonal dynamics in organizations.